A new retarding agent of building gypsum hardening / Naujas statybinio gipso kietėjimo lėtiklis - Kazragis, Algimantas; Marčiukaitis, Glntaras; Jurkėnas, Gediminas (Journal of Civil Engineering and Management, 1996)
In order to inhibit the process of setting and hardening of building gypsum, retarding agents are used. They: 1) decrease the solubility of gypsum semihydrate (e.g. ammonia); 2) form compounds of lower solubility on the surface of gypsum grains (sodium and potassium phosphates, tetraborate, boric acid); 3) are absorbed on gypsum grain surface and inhibit the formation of crystal nuclei (sulphite alcohol ferment, keratin).The materials mentioned above have some disadvantages: 1) long duration of preparation (lying, boiling, filtering) and uncertainty of formulae (glue solutions); 2) layering of gypsum additions mixtures and decrease of mechanical resistance of hardened gypsum (phosphates, borates); 3) process complications caused by necessity of water heating that leads to uncertain influence of additions when the conditions for maintaining constant temperature of the mixture are absent (hot running water).New retarding agent, inhibiting the hardening of building gypsum without disadvantages listed above is created. The effect of the retarding agent is caused by the formation of clathrate compounds. The retarding agent consists of carbamide and inorganic stabilising addition, in ratio 40:1. The duration of the complete hardening of building gypsum can be prolonged by the retarding agent up to 90 min.Article in Lithuanian.First Published Online: 26 Jul 2012